Hackathon - website backup - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The hackathon’s site (http://hackathon.ccafs.cgiar.org/) is no longer available online as it was financed by the CGIAR Climate Change, Agriculture, and Food Security (CCAFS) Program, which was closed in 2021.